Reaction of aggression of Сhaffinch (Fringilla coelebs L. 1758) and behavioral acts at watering places in natural conditions and anthropogenically changed territories - Маркова, А. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The data regarding aggression acts of the Chaffinch (Fringilla coelebs) at watering places during the nesting period in the Kaniv Natural Reserve and the State Dendrologicsl Park “Aleksandria” are provided. The connection of aggression and behavior acts at watering places has been found out in the Kaniv Natural Reserve, which has not been observed within the dendrological park area. Interspecific and intraspecific contacts of the finches have been analyzed. Intraspecific aggression is more highly expressed within natural park territory, and interspecific aggression – in dendrological park conditions. In general, there has been found out 20 species of birds, to which the finch aggressively responds. In natural conditions the aggression ratio of finches highly correlates with the presence and number of Great tit (Parus major), Marsh tit (Parus palustris) and Blackcap (Sylvia atricapilla), in anthrophogenically changed territories – only with the presence and number of Great tit. Critical distance of aggression in intraspecific conflicts has been found out to be 50 cm. Critical distance in interspecific conflicts varies between 15 cm and 1.5 m.